The scope and bounds of transitional justice and the Canadian Truth and Reconciliation Commission - Nagy, Rosemary L. (International journal of transitional justice, 2013)
The Canadian Truth and Reconciliation Commission (TRC) on Indian residential schools allows us to rethink the scope and bounds of transitional justice. Once we expand our notions of injustice and transition, the Canadian case is not so far apart from paradigmatic cases, which too often overlook structural violence. The article argues for settler decolonization as a path of reconciliation and in so doing directly engages structural violence and instantiates theoretical arguments to more securely anchor the field of transitional justice to positive peace. The article analyzes the decolonizing potential of the TRC in its ability to invoke ‘social accountability’ through its approach to truth and in its grassroots potential. Although the TRC has some capacity to advance decolonization, its progress is hampered by the conservative political environment, its weak public profile and to some degree its own emphasis on survivor healing, which provides a ready focal for settlers to individualize Indian residential schools violence as something of the past. Yet, Indigenous healing is intrinsically connected to structural transformation and reconciliation depends upon remedying colonial violence in the present.